Solution of substance abuse and domestic violence mathematical model using Homotopy pertubation method - Azuaba*, E.; Oluwafemi *†‡, T. J.; Akinwande †, N. I.; Bako, D.; Dayap§, J. (International Journal of Mathematical Analysis and Modelling, 2023)
In this study, homotopy perturbation method was applied for the approximate solution of a mathematical model of substance abuse and domestic violence. The system of model equations developed was transformed into series of differential equations which enables the series to converge which gives the approximate solution required.